Architectural heritage and gender inequality in the city of Salta - Gonza, Cinthia Natalia (2019)
The article questions and analyzes some elements of the architectural heritage of the city of Salta, Argentina, from the genealogical perspective and gender studies. The historical heritage is understood as a device that articulates a type of rationality showing subordination of women in the public space. This problem turns out to be a challenge and a focal point at the moment of thinking and creating more egalitarian cities.